2009
DOI: 10.1016/j.taap.2008.11.002
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun/AP-1 pathway-mediated cyclin D1 expression participates in low dose arsenite-induced transformation in mouse epidermal JB6 Cl41 cells

Abstract: Arsenic is a well-documented human carcinogen associated with skin carcinogenesis. Our previous work reveals that arsenite exposure is able to induce cell transformation in mouse epidermal cell JB6 Cl41 through the activation of ERK, rather than JNK pathway. Our current studies further evaluate downstream pathway in low dose arsenite-induced cell transformation in JB6 Cl41 cells. Our results showed that treatment of cells with low dose arsenite induced activation of c-Jun/AP-1 pathway, and ectopic expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 50 publications
2
58
0
Order By: Relevance
“…AP-1 is a canonical regulator of transcription of cyclin D1 (37). Deficiency of XIAP E3 ligase activity repressed AP-1 transcriptional activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AP-1 is a canonical regulator of transcription of cyclin D1 (37). Deficiency of XIAP E3 ligase activity repressed AP-1 transcriptional activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because previous studies have demonstrated that NFB and AP-1 are two key transcription factors in the mediation of cyclin D1 transcription (23,36,37) and because BIR domains of XIAP have been reported to be crucial for NFB activation (38), cytoplasmic and nuclear extracts were prepared, and the nuclear/cytoplasm distribution of NFB components (p65 and p50) was examined by Western blot in comparison with the distribution of another transcription factor, c-Jun, which is a major component of AP-1, in the transfectants. Consistent with the reported BIR domain regulation of NFB activation (38), our results showed that XIAP deletion or BIR domain deficiency reduced the nuclear/cytoplasm ratio of either p65 or p50 protein levels in comparison with those in WT cells, whereas RING domain deletion did not show this regulatory effect (Fig.…”
Section: Xiap and Its E3 Ligasementioning
confidence: 99%
“…32,33 Although cyclin D1 was associated with proliferation by arsenic in human primary keratinocytes, 19 it remains an open question whether cyclin D1 contributed exclusively to the proliferation of keratinocytes. This study indicates that arsenic increases mitochondrial functions and proliferation through up-regulation of mtTFA, which is likely independent of cyclin D1 (Figures 7 and 8).…”
Section: Discussionmentioning
confidence: 99%
“…The human SP1 fragments were amplified by primers 5Ј-CCAGGCCCTCCAAGC-AGCAC-3Ј and 5Ј-GCTGCTGGTCTGCCCCAAGG-3Ј. The PCR products were separated on 2% agarose gels and stained with ethidium bromide, and the images were visualized and scanned with UV lights with FluorChem SP imaging system (Alpha Innotech Inc.) as described previously (16).…”
Section: Methodsmentioning
confidence: 99%